PENGARUH TABUNGAN DAN DEPOSITO TERHADAP RENTABILITAS BANK PEMERINTAH PERIODE 2008-2011 - Yuniarti, .; Karamoy, Herman (ACCOUNTABILITY, 2013)
In Indonesia, banks are important in supporting economic development. It is given that the banking relation with bank institutions have a strategic function primarily as an institution that bridges the parties who have surplus funds to those who need funds. Funds raised from the public in the form of savings and deposits. Banking sector is one factor that the government's attention because the bank is one of the sources of capital that is needed by the community in running its operations. Bank as one of the government's workers are required to successfully develop its participation.This study uses secondary data published financial statements quartely satae owned banks during the period 2008-2011. This study uses a population of 4 state banks in Indonesia, BNI, BRI, BTN and Bank Mandiri.The analytical method used was multiple linear regression analysis, and hypothesis testing used for statistical testing of the F test dan t test. By using SPSS Software Version 20.0 for windows.The results showed that simultaneous saving and deposit significant effect on the rentability of state-owned banks the period 2008-2011. Partially shows that savings variables affect the rentability of state-owned banks. In partial deposit no significant effect on the rentability of state owned banks. Keywords: savings, deposits, and rentability.